Translation and psychometric validation of the Heart Failure Symptom Tracker (HFaST) - Maria Inês Perez; Joana Seringa; Teresa Magalhães (BMC Cardiovascular Disorders)
Abstract Background Heart Failure (HF) is a global public health issue with high morbidity and mortality rates. Symptom management improves HF patients’ quality of life and demonstrates a potential reduction in hospitalisation, particularly among individuals aged 65 and over. Early identification of patients at higher risk of hospitalisation is essential to guide patient-centred interventions. This study aimed to translate, cross-culturally adapt and evaluate the psychometric properties of the Heart Failure Symptom Tracker (HFaST) tool for the Portuguese population. Additionally, it aimed to test the hypothesis that higher scores of the HFaST are associated with increased hospitalisations due to HF decompensation. Methods This cross-sectional study was conducted in two phases. The first phase involved the linguistic translation and cross-cultural adaptation of the HFaST tool into European Portuguese. Content validity was assessed by a panel of ten experts, who evaluated the clarity, relevance and equivalence of the pre-final version. A pre-test, using cognitive interviews with a sample of forty individuals was conducted to assess the item comprehensibility of the adapted tool. The second phase involved the psychometric validity in a sample of sixty HF patients. Participants completed a demographical and clinical assessment, the Portuguese version of the HFaST tool and the Portuguese version of the KCCQ-23 questionnaire. Additionally, the association between HFaST scores and HF hospitalisations were analysed. Results Equivalence between versions showed substantial to perfect agreement, with Fleiss’ k ranging from 0.678 to 1.000. Necessary adjustments were performed. Pre-test confirmed 95% comprehensibility. Internal consistency was acceptable, with a Cronbach’s Alpha of 0.724, moderate to strong inter-item correlations, and significant correlations between the HFaST and the KCCQ-23 items were observed. Higher HFaST scores were significantly associated with increased hospitalisations, highlighting its role as a predictive tool for clinical risk stratification. Conclusions The Portuguese version of the HFaST demonstrated to be a reliable and valid self-management tool for HF patients in Portugal. By predicting the likelihood of hospitalisation risk, the HFaST enables clinicians to implement early interventions, potentially reducing hospital admissions, improving patients’ outcomes and contributing to a better quality of life. Clinical trial number not applicable.